Comissão de Integração Ensino-Serviço Regional de Imperatriz: implantação e contribuições para Política de Educação Permanente em Saúde no Estado do Maranhão - Freitas, Wellington Queiroz de (2023)
Permanent Health Education (EPS), as a training and development strategy for workers for the Unified Health System (SUS), was established as a policy in 2004, through ordinance no. 198, and redefined by ordinance no. 1. 996 of 2007. It aims to contribute to the necessary transformation of work processes and health practices, in accordance with the principles of decentralization of the SUS, which define guidelines and strategies for the implementation of the National Policy for Permanent Education in Health (PNEPS), establishing the Permanent Teaching-Service Integration Commissions (CIES) as permanent bodies that participate in the formulation, conduct and development of PNEPS. In this sense, this research aimed to contribute to the process of implementing CIES in the Imperatriz health region, aiming to strengthen PNEPS in the state of Maranhão (MA). This is an Action Research with an evaluative study, whose theoretical framework is based on the assumptions of PNEPS. The subjects participating in this research were managers, workers, representatives of educational institutions with courses in the area of health and social control in the SUS, who participate in the Teaching-Service integration processes in the Health Region of Imperatriz/MA. The data were collected during the interventions and the workshop with the central theme Permanent Education in Health, from April to October 2023, which made it possible to identify the profile of these participants and their perceptions about PNEPS, in addition to contributing to the implementation of CIES Imperatriz/MA Region. As a product, a booklet was prepared for managers of the Unified Health System (SUS) on Permanent Health Education and guidance on how to implement a Regional CIES. The results present a considerable number of courses in the health area in the Distance Education modality (EAD) offered by Higher Education Institutions (HEIs) in the region. It was also observed that research participants were unaware of the importance of Continuing Health Education. It is expected that the results of this research can support strategies for strengthening EPS and establishing CIES in all Health Regions in the state of Maranhão.